3D Scanning Technology as a Key for Quality Control and Precision in Civil Engineering 3DCP Construction - Vaněk, Vojtěch; Penčík, Jan (ECON Publishing, 2025)
This paper focuses on new application methods, with an emphasis on Additive Manufacturing and especially on 3D Concrete Printing. As concrete printing is a “living material”, there is a need for continuous quality and accuracy control, with an emphasis on the verification of finished rigid structural elements made by 3DCP. The paper presents different methods and technologies for the use of 3D scanning, analyses the use of scanning in practice and discusses the main challenges and future directions.
Keywords: 3D Concrete Printing; 3DCP; 3D Scanning Technology; 3DST; Laser Scanning; Photogrammetry